IDENTIFIKASI IKAN BANDENG BERFORMALIN DAN TIDAK BERFORMALIN MENGGUNAKAN GRAY LEVEL CO-OCCURENCE MATRIX DENGAN KLASIFIKASI K-NEAREST NEIGHBOR - Muhammad Harris, - (2019)
Fish is a food that contains high protein and contains essential amino acids needed by the body. One of the fish consumed by Indonesians is milkfish. In aggregate the participation rate is more than 10 percent. Along with the importance of the fisheries sector in Indonesia, there are public concerns about fishery products that can adversely affect human health. For example, like fish containing formalin as a preservative, the concern about the appearance of formalin fish is exacerbated by the people's inability to distinguish between formalin and non-formalin fish. Therefore, in this study a system will be developed to differentiate milkfish containing formaldehyde and not containing formaldehyde. And in this study the author will use the Gray Level Co-Occurence Matrix (GLCM) method for feature extraction and also K-Nearest Neighbor (KNN) as its classification with the MATLAB programming language. The image processing used is the image of milkfish eyes with a total of 80 milkfish data images which are divided into 80% training data and 20% testing data, so that the author has 64 training data images and 16 testing data images. From this study the authors produced the best accuracy of 93.75% at the value of k = 1